FOCAL MECHANISMS OF SEISMIC EVENTS ON MARS - MALYTSKYY, Dmytro; GNYP, Andriy; ASTASHKINA, Oleksandra; ZABRODSKA, Natalia; PAK, Ruslan; IGNATYSHYN, Vasil; FURMAN, Vitaliy; NIKULIN, Valery (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
According to data obtained by NASA’s InSight mission, Mars appears to be a seismically active planet. In this paper, we focus on two events – S0235b and S1222a, the second of which (May 4, 2022, Mw 4.7) is the strongest of all recorded by the broadband seismic station ELYSE, the only one on Mars. Epicentral distance of S1222a was 37.2°. We determine the focal mechanisms of events using the method based on the model of a point source in an elastic horizontally layered medium. Seismic moment tensor is determined by inversion of high-frequency seismograms calculated by the matrix method for direct waves. The process involves convertion into displacements in the time domain after integration over frequency and wavenumber. The use of only direct P- and S-waves, which are less sensitive to propagation effects than reflected and converted ones, significantly improves accuracy and reliability of the proposed method. For the event S1222a, the match of the synthetic forms of direct waves to the observed ones is demonstrated. A comparative analysis of the focal mechanisms obtained for the S0235b event by inversion of only direct waves and by full direct inversion is also presented.